REMOVING THE PHYSICAL BODY FROM INTERACTION - A PHENOMENOLOGICAL INVESTIGATION INTO LAYPEOPLE SHARING SELF-TRACKED EXERCISE DATA ON SOCIAL NETWORK SITES WHEN THEY FEEL UNEASY EXERCISING WITH PEOPLE - Grønborg, Joeb Høfdinghoff (AoIR Selected Papers of Internet Research, 2018)
Self-tracking applications (apps) like Endomondo, Runkeeper and Strava have made it effortless for laypeople to measure their exercise activity and turn it into detailed data on running time, distance, average pace, calories burned etc. The users can share the exercise data with personal networks of users (often named friends) on the apps’ internal social network sites (Ellison & boyd, 2013) or external social network sites such as Facebook or Twitter. Few studies, however, have shed light on how people use self-tracking in their everyday lives (Lupton, 2016) – e.g. why people share exercise data on social network sites. Some people feel uneasy by exercising with – or in the presence of – people. In this paper, I provide a thick description of people that bypass their struggle with social exercise by sharing exercise data on social network sites. I utilize the lived experience of two female newcomers to exercise, Amanda and Dorte, to illustrate this. Firstly, using the philosopher and medical doctor Drew Leder’s phenomenological investigations into embodiment, I analyze how the females’ bodies dys-appear (Leder, 1990) when they exercise near/with people. Secondly, I examine how their networks of friends function as a beneficial form of exercise sociality that encourages Amanda and Dorte’s exercise activity. My empirical data originates from an exploratory, interview study of 12 Danish, recreational athletes’ experiences with exercise-related self-tracking apps.